2017
DOI: 10.1002/ejic.201700716
|View full text |Cite
|
Sign up to set email alerts
|

Electronic‐Structure Calculations of Cation‐Ordered II‐III Layered Double Hydroxides: Origin of the Distortion of the Metal‐Coordination Symmetry

Abstract: Cation ordering brings down the crystal symmetry and introduces distortion into the coordination polyhedra around the divalent cations. In particular, edge sharing of the differently sized [M(OH)6] polyhedra causes a non‐uniform distension of the array of hydroxy ions. The question arises as to whether this distortion has its origin in the Jahn–Teller distortion of metal coordination or a 2D “Peierls”‐type distortion of the array of hydroxy ions. To address this question, DFT calculations were performed on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…37 The weakening of the (110) plane is due to the presence of transition metal (Cu 2+ ), that disrupts the octahedral cation coordination and, consequently, leads to poor long-range ordering (known as the Jahn–Teller distortion effect). 27,39 It was observed that the intensity of the (110) plan decreased as the urea content decreased (Fig. 1), reflecting the role of urea percentage on the cation ordering within the layered structure.…”
Section: Resultsmentioning
confidence: 94%
“…37 The weakening of the (110) plane is due to the presence of transition metal (Cu 2+ ), that disrupts the octahedral cation coordination and, consequently, leads to poor long-range ordering (known as the Jahn–Teller distortion effect). 27,39 It was observed that the intensity of the (110) plan decreased as the urea content decreased (Fig. 1), reflecting the role of urea percentage on the cation ordering within the layered structure.…”
Section: Resultsmentioning
confidence: 94%
“…Unlike II–III LDHs , where structural information for SO 4 -LDHs is well established, there are limited reports on I–III LDHs. In this work, the SO 4 -LDH ( d spacing 10.6 Å) exhibits turbostratic disorder, resulting in diminished hkl reflections, which yield little structural information.…”
Section: Resultsmentioning
confidence: 99%
“…In previous literature, the Jahn-Teller effect of Cu-based LDHs has been widely reported. 75 In general, the selectivity of CH 3 OH for photocatalytic CO 2 reduction over LDHs should be evaluated by considering both DG PDS for CO 2 reduction to CH 3 OH* and DG for the further reduction of CH 3 OH*.…”
Section: Reaction Mechanism Of (Zncu) 2 Ga-no 3 -Ldhmentioning
confidence: 99%